Modelling of a GFRP adhesive connection by an imperfect soft interface model with initial damage. (1st May 2020) - Maurel-Pantel, A.; Lamberti, M.; Raffa, M.L.; Suarez, C.; Ascione, F.; Lebon, F.
Abstract: In this paper a methodology to model a GFRP adhesive connections by using an imperfect soft interface model is presented. The model based on Kachanov's theory considered a cracked thin adhesive. Within this framework, the mechanical properties and the initial damage (diffuse initial cracks) of the adhesive layer has been experimentally evaluated. With a modified Arcan system, static tests are performed on adhesively bonded assemblies in tensile and shear solicitation mode considering three different adhesive thicknesses. The experimental results highlighted how the thickness of adhesive influences the mechanical strength and stiffness of the bonded connection. CT-scans are performed to measure the porosity rate in the adhesive layer. Furthermore, the excellent comparison of numerical and experimental data of an adhesive GFRP bonded connections allow us to consider the imperfect soft interface model proposed as highly competitive to evaluate complex structure performance in civil engineering context. A parametric analysis has been proposed to provide a formula able to describe the full response of the structure at varying adhesive property.